The Growth of Islamic Banking and SMEs Financing in Indonesia - ahmad syarif (HUMAN FALAH: Jurnal Studi Ekonomi dan Bisnis Islam, 2016)
This research presented Islamic Banking which continuously experienced growth in the banking system in Indonesia. Banking was expected to strengthen the SMEs in accessing the business financing with the concept of profit and loss sharing. This research was done to find out whether the increasing growth of Islamic Banking gave a positive response to the SMEs financing and other variables in line with the rising of Islamic Banking portofolio. The study was based on secondary data and mostly collected from the Islamic Banking Statistics 2011-2015 published by Bank Indonesia. Method of Vector Error Correction Model (VECM) was used for data analysis and variables were financing in SMEs (UKM), depositor funds (DPK), non performing financing (NPF), number of worker (PKJ) and financing to desposit ratio (FDR). The result of the dynamic response analysis that the variables of Islamic Banking contributed positively to the financing of SMEs in Indonesia. DPK (2.17%), FDR (1.26%), NPF (1.2%) and PKJ (4.68%) contributed to the SMEs growth. The interesting findings were the similarity of the results of VECM Analysis, IRF Analysis and Variance Decomposition Analysis who asserted the need of Depositor Funds (DPK) as the driver of SMEs growth in Indonesia.